Reappearance from Obscurity: Mammalian Rad52 in Homologous Recombination - Hanamshet, Kritika (Genes (Basel), 2016)
Homologous recombination (HR) plays an important role in maintaining genomic integrity. It is responsible for repair of the most harmful DNA lesions, DNA double-strand breaks and inter-strand DNA cross-links. HR function is also essential for proper segregation of homologous chromosomes in meiosis, maintenance of telomeres, and resolving stalled replication forks. Defects in HR often lead to genetic diseases and cancer. Rad52 is one of the key HR proteins, which is evolutionarily conserved from yeast to humans. In yeast, Rad52 is important for most HR events; Rad52 mutations disrupt repair of DNA double-strand breaks and targeted DNA integration. Surprisingly, in mammals, Rad52 knockouts showed no significant DNA repair or recombination phenotype. However, recent work demonstrated that mutations in human RAD52 are synthetically lethal with mutations in several other HR proteins including BRCA1 and BRCA2. These new findings indicate an important backup role for Rad52, which complements the main HR mechanism in mammals. In this review, we focus on the Rad52 activities and functions in HR and the possibility of using human RAD52 as therapeutic target in BRCA1 and BRCA2-deficient familial breast cancer and ovarian cancer.